THE SEER AND THE SEEN: A SURVEY OF TOPICS FOUND IN PALANTIR PATENTS - Iliadis, Andrew James; Acker, Amelia (AoIR Selected Papers of Internet Research, 2021)
Palantir is one of the most secretive technology firms in the US. The company supplies information technology (IT) solutions to governments, nonprofits, and corporations, focusing on data integration and surveillance services. To investigate Palantir’s opaque technology practices, this article presents findings from a topic modeling of Palantir patents (n=155) filed from 2006-2019 in the US, Germany, Australia, UK, and EU. This approach follows recent literature that uses patents as data for researching opaque IT firms. We begin by summarizing scholarship on Palantir and IT for policing, intelligence, and security. Our findings show that Palantir’s IT produces infrastructural layers of meaning/context via metadata that are wrapped ‘on top’ of previously held legacy data. We thus use the concept of infrastructuring to understand Palantir’s practices, where information standards like metadata are theorized as phenomena for structuring social worlds. The paper ends by offering action items for future research into opaque IT firms.